If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + z(9) = 9 Reorder the terms for easier multiplication: 6 + 9z = 9 Solving 6 + 9z = 9 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 9z = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 9z = 9 + -6 9z = 9 + -6 Combine like terms: 9 + -6 = 3 9z = 3 Divide each side by '9'. z = 0.3333333333 Simplifying z = 0.3333333333
| 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 4y-a=5a+6(3-y) | | Ln40/ln4 | | 2-(1/3)t | | 6+z(9)=9 | | -4(-3x-8)-4x+8= | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -8x+3+3x=13 | | 7x=3(3x-4) | | 7x+5(4-2x)=5 | | (x-35)+90+43=180 | | (8x+4)(8x-4)=y | | -6x+7(2x+6)=142 | | -90-6x=48-12x | | -100=n+8 | | 7x+5(4-2x)=5 | | (8x+4)(8x-4)=y | | -4(-3x-8)-4x+8= | | (x-35)+90+43=180 |